Impact of copper toxicity on stone-head cabbage (Brassica oleracea var. capitata) in hydroponics - Sajid Ali; Muhammad Shahbaz; Ahmad Naeem Shahzad; Hafiz Azhar Ali Khan; Moazzam Anees; Muhammad Saleem Haider; Ammara Fatima (PeerJ, 2015)
Arable soils are frequently subjected to contamination with copper as the consequence of imbalanced fertilization with manure and organic fertilizers and/or extensive use of copper-containing fungicides. In the present study, the exposure of stone-head cabbage (Brassica oleracea var. capitata) to elevated Cu2+ levels resulted in leaf chlorosis and lesser biomass yield at ≥2 µ M. Root nitrate content was not statistically affected by Cu2+ levels, although it was substantially decreased at ≥5 µ M Cu2+ in the shoot. The decrease in nitrate contents can be related to lower nitrate uptake rates because of growth inhibition by Cu-toxicity. Shoot sulfate content increased strongly at ≥2 µ M Cu2+ indicating an increase in demand for sulfur under Cu stress. Furthermore, at ≥2 µM concentration, concentration of water-soluble non-protein thiol increased markedly in the roots and to a smaller level in the shoot. When exposed to elevated concentrations of Cu2+ the improved sulfate and water-soluble non-protein thiols need further studies for the evaluation of their direct relation with the synthesis of metal-chelating compounds (i.e., phytochelatins).